The Influence of the Need for Self-Actualization, Personal Control and Interpersonal Communication on Employee Work Performance at the Regional Office of the Directorate General of Treasury of North Sulawesi Province - Reyhan G. Miliano; Greis M. Sendow; Yunita Mandagie (Formosa Journal of Applied Sciences, 2023)
This research aims to determine the influence of the need for self-actualization, personal control and interpersonal communication on work performance at the Office of the Directorate General of Treasury, North Sulawesi Province. Data collection carried out in this research used a questionnaire, with multiple linear analysis techniques. The questionnaire in this research is divided into two parts, the first contains information about the respondent's personal data and the second contains information about the research variables, namely Self-Actualization Needs, Personal Control, Interpersonal Communication, and Work Performance. This research uses a quantitative method. The sampling technique in this research uses a simple random sampling technique which is a random sampling technique. The results of this research found that self-actualization has a positive and significant effect on work performance, personal control has a positive and significant effect on work performance, and interpersonal communication has a positive and significant effect on work performance.